Radiotherapy and Eribulin Mesylate for Mediastinal Node Metastasis from Breast Cancer-A Case Report - Ishizuka, Mariko; Tsubota, Yu; Sueoka, Noriko; Chiba, Tsukuru; Miyata, Mami; Yoshikawa, Katsuhiro; Yamamoto, Daigo (Gan to kagaku ryoho, 2018)
A69 -year-old woman was diagnosed as having local advanced breast cancer. She was treated with neoadjuvant chemotherapy( AC followed by paclitaxel)and followed up with left total mastectomy with axillary lymphadenectomy for breast cancer(pT3N1aM0, Stage ⅢA, ER positive, PgR positive, and HER2 negative). She received adjuvant therapy with chest wall irradiation and an aromatase inhibitor. Two years after the mastectomy, mediastinal lymph node and rib metastases and dissemination appeared. We changed the regimen to capecitabine. She continued the capecitabine therapy for 7 years and was found to have multiple lung metastasis. Therefore, we chose eribulin mesylate therapy. Ten days after eribulin mesylate (1.0mg/body)was first administered, she suddenly had difficulty breathing, and chest CT revealed left low lobe atelectasis. The superior mediastinal lymph node had grown rapidly and compressed the left main bronchus and superior vena cava. To reduce the lymph node size, we started radiotherapy(50 Gy/25 Fr)for the superior mediastinal area in addition to the eribulin mesylate therapy. After the radiotherapy, chest CT revealed a remarkable reduction of lymph node size and full pulmonary reexpansion. One year after the radiotherapy, she is continuing treatment without systemic progression.